An antiferromagnetically coupled heterometal Cu6Fe wheel - Saiki, Ryo; Yoshida, Norifumi; Hoshino, Norihisa; Newton, Graham N.; Shiga, Takuya; Oshio, Hiroki (Chemical Society of Japan, 2017)
A heterometal Cu6Fe wheel molecule, [CuII6FeIII(HL)6- (OH)2(OCH3)4](NO3)3¢6H2O (1¢6H2O) (H2L = 1-(2-pyridine) 3-(2-pyrrole)acetylacetone) was synthesized by the one-pot reaction of H2L with copper and iron sources. X-ray structural analysis reveals that the heptanuclear wheel cluster consists of a central Fe(III) ion surrounded by six Cu(II) ions, linked through methoxo- and hydroxo-bridges. Cryomagnetic studies indicate intramolecular antiferromagnetic interactions were operative.